Concurrent validity and reliability of different technologies for sprint-derived horizontal force-velocity-power profiling - Cormier, P.; Tsai, M. C.; Meylan, C.; Agar-Newman, D.; Epp-Stobbe, A.; Kalthoff, Z.; Klimstra, M. (The Journal of Strength and Conditioning Research, 2023)
This study evaluated the validity and reliability of common systems to assess sprint-derived horizontal force-velocity-power (FVPH) profile metrics. Two double constellation athlete monitoring systems (STATSports Apex, Catapult Vector S7) and one timing gate system were compared with a radar gun for the computation of FVPH metrics. Intersystem validity was assessed using intraclass correlation coefficients (ICC), Pearson's correlation coefficients (R2), and Bland-Altman plots with absolute and percent agreement. Intrasystem reliability was assessed with agreement bias and ICC. STATSports demonstrated moderate agreement for F0, Pmax, t, and Drf (8.62, 6.46, -9.81, and 9.96%, respectively) and good agreement for V0 and MSS (-2.18 and -1.62%). Catapult displayed good agreement across all metrics (F0, V0, Pmax, MSS, t, and Drf: -0.96, -0.89, -1.85, -0.84, 0.38, and -0.27%, respectively). Timing gates demonstrated good agreement with V0 and MSS (-2.62 and -1.71%) and poor agreement with F0, Pmax, t, and Drf (19.17, 16.64, -20.49, and 20.18%, respectively). Intrasystem reliability demonstrated good agreement (<2% bias) with very large to near-perfect ICC (0.84-0.99) for Catapult and STATSports systems. Overall, GPS/GNSS 10 Hz technology is reliable across devices and can provide moderate-to-good accuracy of FVPH metrics in single maximal effort sprints. However, Catapult provided better agreement for more FVPH metrics than STATSports, which may be related to differences in proprietary algorithms. Also, modeling timing gate data using current FVPH profiling techniques results in poor bias that requires greater investigation. GPS/GNSS data can be used for FVPH profiling, which could inform performance and rehabilitation processes.